2021
DOI: 10.1002/masy.202000233
|View full text |Cite
|
Sign up to set email alerts
|

Filler Content Effect on Water Uptake and Thermal Stability of Poly(3‐Hydroxybutyrate‐Co‐3‐Hydroxyhexanoate)/Microcrystalline Cellulose Biocomposites

Abstract: In this study, biocomposites of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx)/cellulose microcrystalline (MCC) extracted from olive husk flour are prepared by melt compounding at various filler content ratios, i.e., 10, 20, and 30 wt%. The effect of the MCC content on the morphology, thermal stability, crystallinity, and water uptake of the PHBHHx biocomposites is investigated. The results showed that the addition of MCC to PHBHHx decreased the thermal stability of the biocomposites compared to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This is while the incorporation of PLA with PHBH could boost the modulus and strength of the PHBH. Therefore, their corresponding blends can feature a good compromise between stiffness and toughness, offer good thermal resistance, and quickly biodegrade in a natural environment.In PHBH composites, Dehouche et al[98] demonstrated that adding hydrophilic constituents (e.g., cellulose or natural fibers) inside the PHBH matrix can facilitate water absorption, which further accelerates polymer degradation in natural environments. Xu et al[99] studied the biodegradation effect of regenerated cellulose addition.…”
mentioning
confidence: 99%
“…This is while the incorporation of PLA with PHBH could boost the modulus and strength of the PHBH. Therefore, their corresponding blends can feature a good compromise between stiffness and toughness, offer good thermal resistance, and quickly biodegrade in a natural environment.In PHBH composites, Dehouche et al[98] demonstrated that adding hydrophilic constituents (e.g., cellulose or natural fibers) inside the PHBH matrix can facilitate water absorption, which further accelerates polymer degradation in natural environments. Xu et al[99] studied the biodegradation effect of regenerated cellulose addition.…”
mentioning
confidence: 99%
“…The use of cellulosic fibers is now becoming essential in biocomposites not only in terms of performance but also to preserve the biodegradability character of the materials. 23,24 Indeed, cellulose nanocrystals, [25][26][27] fibrillated nanocellulose, 28 porous cellulose, 29 and microcrystalline cellulose extracted from olive husk flour 30 have been used to improve the performance properties of polymer composites. Notwithstanding, the elastic modulus of the filled composites were increased, while the thermal stability was less affected.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] As a matter of fact, polyhydroxyalcanoates (PHAs) are naturally synthesized polyesters that attracted a lot of attention owing to their extensive array of properties, which are similar to those of polyolefins. [5,6] A long with this family of bio-polyesters, PHB-HHx is a random block copolymer, which exhibits better performances compared with other PHAs such as toughness, and ease DOI: 10.1002/masy.202100272 of processability. [7] However, its high cost and poor stiffness limit its widespread applications.…”
Section: Introductionmentioning
confidence: 99%